Visual imaginary of Human Rights and digital iconography - Martorell, Sandra; Lopezosa, Carlos; Codina, Lluís (Cuadernos de Documentación Multimedia, 2025)
Human rights were proclaimed in 1948. Since then, a collective imaginary has been forged around this concept. The objectives of this research are, on the one hand, if there is a correlation between the images that make up the visual imaginaries and those offered by Google Images, as the hegemonic image search engine. On the other hand, to analyze these images, to see how the idea of human rights is represented in contemporary times and how digital iconographies contribute to continuing to feed this imaginary. To this end, two working methodologies were combined: the constructed week (Riffe, 1993) and the design of an open questionnaire with a mixed response option (textual or graphic) applied to a group of people. The study concludes that: (1) when we speak of human rights in the abstract and in a general way, we obtain mostly symbolic and graphic images with a positive and hopeful connotation; (2) when we concretize, the images we obtain no longer show ideals of the future, but rather are photographic images, which show us a cruder reality and remind us that there is still much to be done in the area of human rights